Investigating the extent of information technology usage in Malaysian batik industry / Yap May Lin, Yap Bee Wah and Jasber Kaur Gian Singh - Yap, May Lin; Yap, Bee Wah; Gian Singh, Jasber Kaur (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2006)
In this new information technology era, business enterprises in Malaysia should capitalize on the use of information technology (IT) to gain competitive advantage and bring their businesses to the global forefront. This paper discusses the extent of IT usage in the Malaysian Batik Industry. A survey study involving eleven batik companies in the Klang Valley was carried out. Information was also gathered via interviews with four related organization. Survey results indicated that communication via telephone is still the major mode of communication with suppliers, producers and customers Payment by cheque is still the most favored mode of payment and very few batik companies provide online payment facilities. Only four batik companies have set up their own websites. The services they wish to add to their websites are shopping cart, online payment and immediate credit card validation services. The main benefits they gain from their websites are faster and more efficient communication with customers while the two main problems they face are funding and lack of expertise in their company to maintain the website. Results of this study also show that improved sales, profitability, competitive position and recognition of market brand are significantly correlated with the batik company commitment to using IT in their business.